2021
DOI: 10.1038/s41598-021-94635-1
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and risk factors of human papillomavirus infection: an outpatient population-based study in Changsha, Hunan

Abstract: This cross-sectional study investigated the characteristics of cervical HPV infection in Changsha area and explored the influence of Candida vaginitis on this infection. From 11 August 2017 to 11 September 2018, 12,628 outpatient participants ranged from 19 to 84 years old were enrolled and analyzed. HPV DNA was amplified and tested by HPV GenoArray Test Kit. The vaginal ecology was detected by microscopic and biochemistry examinations. The diagnosis of Candida vaginitis was based on microscopic examination (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…In Southern China in the Guangdong [ 26 ], Fujian [ 27 ], and Guangxi [ 28 ] provinces, the rates of HPV prevalence vary from 16.2 to 19.5%. Meanwhile, the regions of Western and Middle China have similar HPV rates of 13.5% (Shannxi) [ 29 ], 12.6–15.29% (Sichuan) [ 30 , 31 ], 12.09% (Henan) [ 32 ], 13.56% (Jiangxi) [ 33 ], and 13.88% (Hunan) [ 34 ]. In contrast, HPV prevalence in Eastern China is reported to vary greatly from 10.6% (Jiangsu) [ 17 ] to 22.41% (Zhejiang) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Southern China in the Guangdong [ 26 ], Fujian [ 27 ], and Guangxi [ 28 ] provinces, the rates of HPV prevalence vary from 16.2 to 19.5%. Meanwhile, the regions of Western and Middle China have similar HPV rates of 13.5% (Shannxi) [ 29 ], 12.6–15.29% (Sichuan) [ 30 , 31 ], 12.09% (Henan) [ 32 ], 13.56% (Jiangxi) [ 33 ], and 13.88% (Hunan) [ 34 ]. In contrast, HPV prevalence in Eastern China is reported to vary greatly from 10.6% (Jiangsu) [ 17 ] to 22.41% (Zhejiang) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 21 HPV GenoArray Diagnostic Kit (Hybribio) was used to detect hrHPV infection in cervical smears. This kit has been used in many cervical screening studies, with approval and recommendation from the China National Medical Products Administration for HPV testing . Residual cervical smears after HPV testing were collected and preserved at 4 °C until further Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, comparable percentages of HPV 53 could be identified in HSIL with 8.3%, whereas no HPV 53 was found in LSIL, but 8.3% HPV 53 in CC. Other studies also described frequent detection of the subtype HPV 53 [26,29,30]. Furthermore, HPV 53 is described to occur more likely in multiple infections together with other types [26].…”
Section: Discussionmentioning
confidence: 92%